2019
DOI: 10.1111/ppe.12562
|View full text |Cite
|
Sign up to set email alerts
|

Trends in sociodemographic and health care factors in Portuguese and non‐Portuguese mothers giving birth in Portugal, 1995‐2014

Abstract: Background Time‐trend disparity in adverse pregnancy outcomes according to maternal nationality or immigration status has been well documented. In this study, we investigated time changes in individual‐level risk factors for adverse pregnancy outcomes that have not been given the needed attention. Objective To compare 20‐year trends in sociodemographic, obstetric, health care factors, and adverse pregnancy outcomes in Portuguese and non‐Portuguese women. Methods We studied 2 105 497 livebirths from Portuguese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…One additional paper was identified for full‐text assessment through searching reference lists of included studies, resulting in full‐text assessment being carried out on 54 papers in total. Twenty‐one papers were included in the final review and analysis 28–48 . Figure 1 illustrates the selection process, the number of studies identified and excluded at each stage, and the reasons for exclusion, in line with the PRISMA 2020 statement 49 .…”
Section: Resultsmentioning
confidence: 99%
“…One additional paper was identified for full‐text assessment through searching reference lists of included studies, resulting in full‐text assessment being carried out on 54 papers in total. Twenty‐one papers were included in the final review and analysis 28–48 . Figure 1 illustrates the selection process, the number of studies identified and excluded at each stage, and the reasons for exclusion, in line with the PRISMA 2020 statement 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy complications and adverse birth outcomes linked to social inequalities and unhealthy behaviours are important public health concerns. Maternal age [ 1–3 ], occupation [ 2 ], marital status [ 2 ], education [ 3 ], and lifestyle characteristic [ 4–6 ] are considered to be the most important social determinants of pregnancy outcomes. Advanced age has been shown to be associated with increased risk of pregnancy complications [ 7 ], risk of caesarean section [ 8 , 9 ], stillbirth and adverse neonatal outcomes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%